2021
DOI: 10.26434/chemrxiv-2021-g0ktd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-electron excitation contributions towards primary and satellite states in the photoelectron spectrum

Abstract: The computation of Dyson orbitals and corresponding ionization energies has been implemented within the Equation of Motion Coupled Cluster Singles, Doubles, and Perturbative Triples (EOMCC3) method. Coupled to an accurate description of the electronic continuum via a time-dependent density functional approach using a multicentric B-spline basis, this yields highly accurate photoionization dynamical parameters (cross-sections, branching ratios, asymmetry parameters, and dichroic coefficients) for primary states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…Ionization is a key process in chemistry, as electron removal is used to characterize molecular systems in spectroscopic techniques such as the X-ray photoelectron spectroscopy 38 (XPS), or to follow the advancement of a chemical reaction. [39][40][41][42] Additionally, molecular ionization can be used to initiate and promote new reactive pathways. 43,44 In some recent papers, DePrince, 45 Liebenthal et al 46 and Pavovsevic et al 33,35 demonstrated that ionization potentials and electronic affinities change inside optical cavities.…”
Section: Introductionmentioning
confidence: 99%
“…Ionization is a key process in chemistry, as electron removal is used to characterize molecular systems in spectroscopic techniques such as the X-ray photoelectron spectroscopy 38 (XPS), or to follow the advancement of a chemical reaction. [39][40][41][42] Additionally, molecular ionization can be used to initiate and promote new reactive pathways. 43,44 In some recent papers, DePrince, 45 Liebenthal et al 46 and Pavovsevic et al 33,35 demonstrated that ionization potentials and electronic affinities change inside optical cavities.…”
Section: Introductionmentioning
confidence: 99%